Effectiveness of Local Government Accounting Information Systems: A Study of Training, User Participation, Task Complexity, and Top Management Support - Naiola, Fransiscus Nicodemus; Pah, Viany Cecilia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study, entitled “The Influence of Internal Control Systems and Information Technology…”, highlights how the advancement of information technology in the public sector has encouraged local governments to implement Accounting Information Systems (AIS) to improve the efficiency, effectiveness, and accountability of financial management. AIS plays a crucial role in producing accurate, relevant, and timely financial information as the basis for strategic decision-making. However, the effectiveness of AIS is strongly influenced by several factors, including technical aspects, organizational behavior, and structural support. Effective training can enhance users’ ability to operate the Accounting Information System, thereby improving system effectiveness. Conversely, task complexity can hinder users in utilizing the system, which may reduce its effectiveness. Active user participation can help improve system quality and enhance its effectiveness. Top management support can strengthen the influence of training on system effectiveness by providing adequate resources and support. It can also reinforce the effect of user participation by facilitating communication and collaboration between users and system developers. In addition, top management support may mitigate the negative impact of task complexity on system effectiveness by ensuring sufficient resources and assistance to address task-related challenges. Thus, top management support plays a pivotal role in enhancing the effectiveness of the Accounting Information System.